Flow properties of cellulose and carboxymethyl cellulose from orange peel - Yasar, Fevzi; Togrul, Hasan; Arslan, Nurhan (Elsevier Sci Ltd, 2007)
Cellulose was extracted with 10% NaOH at 35 degrees C for 22 h from defatted, protein, pectin and hemicellulose free, delignified orange peel. The combined effects of temperature and concentration on the viscosity of orange peel cellulose solutions were examined for a temperature range 20-60 degrees C and a concentration range 1-10 kg/m(3). Twenty-eight different models describing the combined effects of temperature and concentration on the viscosity were derived. Models were fitted to the experimental data and the model parameters were deter-mined by nonlinear regression analysis. The orange peel cellulose was converted carboxymethyl cellulose (CMC) by etherification. The theological properties of CMC from orange peel cellulose were determined using a rotational viscometer at five temperatures (10, 20, 30, 40 and 50 degrees C) and six concentrations (10, 15, 20, 25, 30, 35 kg/m(3)), and it was found that CMC solutions exhibited pseudoplastic behaviour. Among the common rheological models, the power law model fits well the shear rate and shear stress data. The consistency index increased with concentration and decrease with temperature. The apparent viscosity was measured, at constant spindle speed, as a function of shearing time. It was found that the CMC solutions were described by the Weltman model and found to exhibit thixotropic behaviour. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: orange peel; cellulose; viscosity; carboxymethyl cellulose; rheology